If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 10 = 2(3x + -11) Reorder the terms: 10 + 4x = 2(3x + -11) Reorder the terms: 10 + 4x = 2(-11 + 3x) 10 + 4x = (-11 * 2 + 3x * 2) 10 + 4x = (-22 + 6x) Solving 10 + 4x = -22 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 4x + -6x = -22 + 6x + -6x Combine like terms: 4x + -6x = -2x 10 + -2x = -22 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + -2x = -22 + 0 10 + -2x = -22 Add '-10' to each side of the equation. 10 + -10 + -2x = -22 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = -22 + -10 -2x = -22 + -10 Combine like terms: -22 + -10 = -32 -2x = -32 Divide each side by '-2'. x = 16 Simplifying x = 16
| 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) | | g=3+h | | 75x-5x=8x+32 | | 667=29j | | 6+4=10 | | 4z+9=45 | | f=2g | | f=29 | | 30t+42m=18600 | | 28g=-364 | | 4z+9=180 | | 27g=-364 | | x+(x+4)+3x=64 | | a+38=469 | | -(x-4)=2+6 | | y=0.6(5)+5.32 | | y=0.6(3)+5.32 | | x-2*3=12 | | z/22=25 | | 42m+30t=18600 | | 1y=0.6+5.32 | | 1=0.6+5.32 | | x^2+26x+108= | | y=0.6(1)+5.32 | | 5x-4yi=15-20i | | (x-3)x+7(x-3)=0 |